A new species of Miroculis Edmunds, 1963 (Ephemeroptera, Leptophlebiidae) from northern Brazil - Neto, Jaime De Liege Gama; Hamada, Neusa (Zootaxa, 2013)
The species of Miroculis Edmunds, 1963 were distributed into four subgenera by Savage & Peters (1983): M. (Miroculis), M. (Yaruma), M. (Atroari) and M. (Ommaethus). These four subgenera occur in Brazil, but of the 10 species recorded from the country, five belong to Miroculis (Miroculis) (Dominguez et al. 2013; Costa & Mariano 2013, Salles et al. 2011). This subgenus is characterized by having the dorsal part of the eyes of the males on a stalks that are longer than wide, with 5 a 20 facets in the longest row (Peters et al., 2008) and is represented by nine species distributed in Brazil, Colombia, Peru, Suriname, and Venezuela (Dominguez et al. 2013; Costa & Mariano 2013). In this paper, Miroculis is reported for the first time in the State of Roraima and a new species of Miroculis (Miroculis) is described based on male imagos from Serra Tepequém.